1994
DOI: 10.1152/ajplung.1994.266.5.l577
|View full text |Cite
|
Sign up to set email alerts
|

Active sodium transport and alveolar epithelial Na-K-ATPase increase during subacute hyperoxia in rats

Abstract: Active Na+ transport and lung edema clearance were studied in a model of lung injury caused by sublethal oxygen exposure. Rats exposed to 85% O2 for 7 days were studied at 0, 7, 14, and 30 days after removal from the hyperoxic chamber and compared with room air controls. In the isolated-perfused, fluid-filled rat lung, albumin flux from the perfusate into the air spaces increased after oxygen exposure and returned to control values after 7 days of recovery. However, permeability to small solutes (Na+ and manni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 0 publications
4
82
0
Order By: Relevance
“…We have previously reported that rats exposed to 85% oxygen for 7 days had increased Na,K-ATPase number and function in AT2 cells, as compared to controls, and this was associated with an increase in active Na + transport in the isolated rat lung model [6,17]. Possibly, in these two models, reactive oxygen species at the alveolar surface initiate a cascade of events that includes increased cytoplasmic calcium [20], cyclic adenosine monophosphate (cAMP), S6 kinases, etc.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We have previously reported that rats exposed to 85% oxygen for 7 days had increased Na,K-ATPase number and function in AT2 cells, as compared to controls, and this was associated with an increase in active Na + transport in the isolated rat lung model [6,17]. Possibly, in these two models, reactive oxygen species at the alveolar surface initiate a cascade of events that includes increased cytoplasmic calcium [20], cyclic adenosine monophosphate (cAMP), S6 kinases, etc.…”
Section: Discussionmentioning
confidence: 92%
“…We have previously observed that rats exposed to 85% oxygen for 7 days exhibited increased active Na + transport across the lung epithelium, as well as increased Na,Kadenosine triphosphate (ATPase) protein function in the alveolar epithelium [6]. Our previous study in the normobaric hyperoxia model and others [7], suggest that upregulation of the Na,K-ATPase in rat lungs are part of the protective mechanism against alveolar flooding.…”
Section: Experimental Protocolmentioning
confidence: 88%
See 1 more Smart Citation
“…Electroneutrality is conserved with Cl Ϫ movement via CFTR in both TI and TII cells, and͞or paracellularly through tight junctions or possibly via an as yet unidentified apical Cl Ϫ -HCO 3 Ϫ exchanger. Because most eukaryotic cells extrude H ϩ to regulate intracellular pH (35), the net effect of uptake via a Cl Ϫ -HCO 3 Ϫ exchange would be to absorb Cl Ϫ and extrude HCO 3 Ϫ , which, when combined with H ϩ in the alveolar lumen, would produce CO 2 , which is exhaled. Extensive experiments characterizing the various channels and the mechanisms by which they are regulated will be necessary to understand the pathways by which anions are transported in the alveolus.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar flooding resulting from cardiogenic pulmonary edema or acute lung injury impairs gas diffusion across the air͞blood barrier; an increase in alveolar fluid clearance restores a normal air͞blood barrier. Alveolar fluid transport from alveolar to interstitial spaces, driven by active Na ϩ transport across the alveolar epithelium (2), can be inhibited either by the addition of amiloride, a Na ϩ channel inhibitor, to the alveolar space, or ouabain, a Na ϩ ,K ϩ -ATPase inhibitor, to the vascular bed (3), suggesting that the alveolar epithelium is the major site of Na ϩ transport and fluid absorption in the adult lung.…”
mentioning
confidence: 99%